Comprehensive Analysis of the Impact of Intrinsic and Extrinsic Motivation on Office Employee Performance in Office Management at a Rental Company - Danish Ammara Azwa; Dewani Azzahra Prasetia Supriadi; Harmon Harmon (Majalah Bisnis & IPTEK, 2025)
This study aims to analyze the influence of motivation on employee performance in office management at PT Surya Sudeco (Tunas Rent), a leading vehicle rental and fleet management company in Indonesia. Employee motivation is considered a crucial factor that can enhance productivity and work effectiveness in a dynamic corporate environment like Tunas Rent, which manages a fleet of over 8,000 units and serves a wide range of corporate clients nationwide. The research employs a quantitative approach, collecting data through questionnaires distributed to employees across various office management divisions. Motivation variables are measured based on intrinsic and extrinsic motivation, while employee performance is assessed through indicators such as achievement of work targets, discipline, and quality of administrative services. The analysis results indicate that motivation has a positive and significant effect on employee performance at Tunas Rent. Enhancing motivation through incentives, continuous training, and a supportive work environment has been proven to encourage employees to perform optimally, ultimately supporting the company’s goal of providing efficient and professional fleet management services. This study emphasizes the importance of management’s role in designing effective motivation strategies to improve employee performance, especially in service companies that heavily rely on coordination and customer service. The findings provide practical contributions for human resource policy development at Tunas Rent and serve as a reference for similar companies in effectively managing employee motivation and performance.